2010
DOI: 10.1111/j.1349-7006.2010.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

New cancer treatment strategy using combination of green tea catechins and anticancer drugs

Abstract: Green tea is now recognized as the most effective cancer preventive beverage. In one study, 10 Japanese-size cups of green tea daily supplemented with tablets of green tea extract limited the recurrence of colorectal polyps in humans to 50%. Thus, cancer patients who consume green tea and take anticancer drugs will have double prevention. We studied the effects of combining ())-epigallocatechin gallate (EGCG) and anticancer drugs, focusing on inhibition of cell growth and induction of apoptosis. Numerous antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 34 publications
1
107
0
1
Order By: Relevance
“…As explained in detail below, EGCG has been proposed as potential adjuvant for cancer therapy. 3 Abbreviations: 5-FU, 5-fluorouracil; ATO, arsenic trioxide; CP, cisplatin; DNR, daunorubicin; DNROL, daunorubicinol; DOX, doxorubicin; EGCG, epigallocatechin-3-gallate; HBMEC, human brain microvascular endothelial cells; HRPC, hormone refractory prostate cancer; HNE, hydroxynonenal; IL, interleukin; IR, ionizing radiation; ROS, reactive oxygen species; TSA, trichostatin A.…”
Section: Egcg As Adjuvant For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As explained in detail below, EGCG has been proposed as potential adjuvant for cancer therapy. 3 Abbreviations: 5-FU, 5-fluorouracil; ATO, arsenic trioxide; CP, cisplatin; DNR, daunorubicin; DNROL, daunorubicinol; DOX, doxorubicin; EGCG, epigallocatechin-3-gallate; HBMEC, human brain microvascular endothelial cells; HRPC, hormone refractory prostate cancer; HNE, hydroxynonenal; IL, interleukin; IR, ionizing radiation; ROS, reactive oxygen species; TSA, trichostatin A.…”
Section: Egcg As Adjuvant For Cancer Therapymentioning
confidence: 99%
“…2 Moreover, its potential use as chemo/radiosensitizer of cancer cells has been proposed, and synergistic effects with different cancer treatments have been shown. 3 In addition, antioxidant and anti-inflammatory properties of EGCG have been associated with the amelioration of adverse side effects derived from cancer therapy. 4 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…About 2.0 mL of methanol solution of each extract at different concentration (2,4,6,8,10 µg/mL) were mixed with 3.0 mL of DPPH methanol solution (20 µg/mL). After an incubation period of 30 min, the absorbance was measured at 517 nm against methanol as blank by using a UV-visible spectrophotometer.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…Several studies revealed that antioxidants are related to other bioactivities e.g. in vitro cytotoxicity in tumor cell and in vivo cytotoxicity in experimental animals and anticarcinogenesis [18][19][20] . Almost all currently available thrombolytic regimens have some vital shortcomings including limited fibrin specificity, noteworthy bleeding tendency and large dose requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory action was associated with the synergistic induction of apoptosis. Suganuma et al (2011) further studied the mechanism of the synergic action and found that a combination of EGCG and sulindac specifically induced upregulated expression of GADD153 and p21 genes in PC-9 lung cancer cells, and the synergistic enhancements of apoptosis and GADD153 gene expression in human non-small cell lung cancer cells by the combination of EGCG and celecoxib were mediated through the activation of the mitogen-activated protein kinases (MAPK) signaling pathway. Based on previous evidence, they presented a new concept: green tea catechins as synergists with anticancer drugs.…”
Section: Structural Modifications Of Catechinsmentioning
confidence: 99%